Lysosomal Cathepsin Release Is Required for NLRP3-Inflammasome Activation by Mycobacterium tuberculosis in Infected Macrophages - Amaral, Eduardo P.; Riteau, Nicolas; Moayeri, Mahtab; Maier, Nolan; Mayer-Barber, Katrin D.; Pereira, Rosana M.; Lage, Silvia L.; Kubler, Andre; Bishai, William R.; D’Império-Lima, Maria R.; Sher, Alan; Andrade, Bruno B. (Frontiers in Immunology, 2018)
Lysosomal cathepsin B (CTSB) has been proposed to play a role in the induction of acute inflammation. We hypothezised that the presence of active CTSB in the cytosol is crucial for NLRP3-inflammasome assembly and, consequently, for mature IL-1β generation after mycobacterial infection in vitro. Elevated levels of CTSB was observed in the lungs of mice and rabbits following infection with Mycobacterium tuberculosis (Mtb) H37Rv as well as in plasma from acute tuberculosis (TB) patients. H37Rv-infected murine bone marrow derived macrophages (BMDM) displayed both lysosomal leakage, with release of CTSB into the cytosol, as well as increased levels of mature IL-1β. These responses were diminished in BMDM infected with a mutant H37Rv deficient in ESAT-6 expression. Pharmacological inhibition of cathepsin activity with CA074-Me resulted in a substantial reduction of both mature IL-1β production and caspase-1 activation in infected macrophages. Moreover, cathepsin inhibition abolished the interaction between NLRP3 and ASC, measured by co-immunoprecipitation and by immunofluorescence imaging in H37Rv-infected macrophages, demonstrating a critical role of the enzyme in NLRP3-inflammasome activation. These observations suggest that during Mtb infection, lysosomal release of activated CTSB and possibly other cathepsins inhibitable by CA07-Me is critical for the induction of inflammasome-mediated IL-1β processing by regulating NLRP3-inflammasome assembly in the cytosol.